Biofilm Forming Ability and Genes Involved in Biofilm Formation of Locally Isolated Intermediate and Saprophytic Leptospira - Jennifer, Jalan (Universiti Malaysia Sarawak (UNIMAS), 2020)
Leptospirosis or widely known as “rat urine disease” is a very common disease in Malaysia. One of the key factors that caused this chronic infection is the ability of the microorganism to produce biofilm formation. Despite its widely known, there is a lack of study on biofilm formation associated with intermediate Leptospira and saprophytic Leptospira. Therefore, the objectives of this study are to quantify the biofilm mass intermediate Leptospira (n=15) and saprophytic Leptospira (n=15) of locally isolated using time course study, to detect the genes involved in biofilm formation by intermediate and saprophytic Leptospira. Finally, to evaluate virulence of Leptospira isolates using Artemia salina in brine shrimp assay. A pathogenic Leptospira spp. was also included as positive control in brine shrimp assay. A full cycle of biofilm formation begins with the attachment on the surface, formation of microcolonies, biofilm mature and back to planktonic cell or cell death. The time course study for intermediate and saprophytic Leptospira was performed for 11 days in accordance to their general biofilm formation process. All of 30 isolates of intermediate (n=15) and saprophytic (n=15) Leptospira formed biofilms on abiotic surface which were represented by microtitre plates and biotic surfaces represented by Dyera costula or Jelutong wood. At day 5, intermediate Leptospira (G7, Leptospira wolffii serovar Khorat strain Khorat H2) was formed stronger biofilm on biotic surface 93.99% than on abiotic surface with 53.33%. While in saprophytic (S19, Leptospira meyeri strain 19CAP), it formed stronger biofilm on biotic surface with 86.67% and abiotic surface with 40%. A significance difference (p<0.05) occurred in biofilm produced between day 1 to day 11 when compared to the negative control (OD). A total of 20 selected strongest biofilm producers of intermediate (n=10) and saprophytic (n=10) were determined and further analysed for identification of biofilm genes. A total of eight genes;icaA, icaB, icaC, icaD, bap, ompL1, flaB and galK genes were studied. Only icaC gene out of eight genes was identified 100% presence of icaC gene (192 bp) using polymerase chain reaction. In brine shrimp assay, pathogenic Leptospira showed the strongest virulence compared to intermediate Leptospira followed by saprophytic Leptospira. Different CFUs of the Leptospira cells were used to treat brine shrimp nauplii and its survival rate was measured 24h, 48h and 72h. It was repeated at least three times and data were statistically analysed using t test where p<0.05 compared to the negative control. In conclusion, this study contributes additional information on the biofilm formation cycle of Leptospira which may be related to their ability to cause infection. It can be further used under clinical practice guidelines to provide impacts in healthcare and public health interventions.